Passiflora cristalina and Passiflora miniata: meiotic characterization of two wild species for use in breeding - Pereira,Telma Nair Santana (2017)
Abstract Passiflora cristalina and Passiflora miniata are two new wild species found in the southern Amazon region. This study aimed to analyze the meiotic behavior of the two species, by meiotic analysis, meiotic index and pollen grain viability, using routine methodologies of the laboratory. By the meiotic analysis, the two species were diploid with 18 chromosomes, and nine bivalents were observed in diakinesis. Laggard chromosomes and fiber spindle problems were the abnormalities observed in both species. The recombination indices were 21.6 and 18.8 for P. cristalina and P. miniata, respectively. The most common abnormal post-meiotic products were triads. The meiotic index and the pollen grain viability for P. cristalina were 90.6% and 98.9%, respectively, and 91.6% and 82.2% for P. miniata, respectively. Based on the results, both species are fertile. Thus, gene transference to sour passion fruit by interspecific hybridization is possible in breeding programs.